A review of moisture migration in bulk material. (17th February 2020) - Chen, Jian; Williams, Kenneth; Chen, Wei; Shen, Jiahe; Ye, Fangping
Abstract: Moisture migration in bulk materials can cause many problems for bulk material handling. The review aims to find an appropriate method for dynamic moisture migration in unsaturated bulk materials during processing. A large amount of research on moisture migration has been done from both macroscopic and microscopic views. From the macroscopic view, moisture migration in bulk materials such as soil, sand, and grain, were relatively well understood based on the diffusion theory and infiltration theories. The microscopic theory, liquid bridge rupture, and vibration were also well developed. The theories and simulation models can be widely used in geotechnology, food engineering and process control of bulk material. However, current research concerns little about dynamic moisture migration in unsaturated bulk material. Some further development of theories and simulation models are needed.